Development of google sites-based learning media using deep learning approach in Buddhist education for grade XI at Negerikaton Pesawaran public senior high school 1 - Dicky Renaldi; Susanto Susanto; Vike Aprilianin Marwintaria Saputri (Universitas Sebelas Maret, 2025)
This study aims to develop Google Sites-based digital learning media with a deep learning approach for the Buddhist Religious Education subject in grade XI at SMA N 1 Negerikaton Pesawaran. The background of this study is the dominance of conventional learning methods that do not utilise digital technology, as well as low student motivation and understanding of the material being taught. Therefore, a digital learning medium is needed that is capable of displaying content in an interactive, visual, and flexible manner so that the learning process becomes more interesting, effective, and efficient. This learning medium is expected to support the learning process for students independently and collaboratively, as well as support the achievement of optimal learning outcomes. The research method used is Research and Development (R&D) at level 3, namely the product development and evaluation stage. The research subjects consisted of seven Buddhist students in Grade XI. Data collection techniques were carried out through observation, interviews, validation by subject matter experts and media experts, and using a one-group pretest-posttest experimental design. To measure the effectiveness of the media, the data were analysed using a Paired Sample T-Test statistical test. The results of the validation by the experts showed that this learning media was